Garfield: a big fat hairy adventure ebook - Davis, Jim (Garfield., 2018)
The Fat Cat stars in KaBOOM!'s first-ever Garfield original graphic novel! When Jon reveals plans to bring Odie to a talent show audition, Garfield decides he can't let Odie get all the spotlight. But when his actions cause Odie to run away, it's up to Garfield to bring Odie back home. Also includes a short story written and illustrated by Liz Prince (Tomboy, Alone Forever).